Optimal Maneuvering and Control of Cooperative Vessels within Harbors. (October 2019) - Gehrt, J.J.; Zweigel, R.; Roy, S.; Büskens, C.; Kurowski, M.; Jeinsch, T.; Schubert, A.; Gluch, M.; Simanski, O.; Pairet-Garcia, E.; Bruhn, W.; Diegel, F.; et al.
Abstract: The publication on hand presents the ongoing developments of a networked control system for maritime application within the joint project GALILEOnautic 2. It is based on the joint project GALILEOnautic, where a system was developed which enables cooperative maneuvering of networked vessels in a harbor environment. The present paper focuses on the planned automation of the research ship DENEB of the German Federal Maritime and Hydrographic Agency (BSH), and discusses the planned evaluation szenario. Therefore, it introduces the required extensions of predecessor system concepts to act on a level close to industrial application. The algorithms will be extended, such that they are capable to a higher number of participating networked ships, are more reliable and can handle error situations. Furthermore, the original cooperative network depended concept will be transferred to a single ship, such that autonomous ships can be integrated in conventional harbor traffic. The design of real-world experiments with an autonomous operating DENEB in the harbor of Rostock are discussed.